SURFACE TEMPERATURE AND ITS RELATION TO THE DURATION OF MACKEREL FISHERY AT KARWAR - Noble, A (Indian Journal of Fisheries, 2011)
Relation between the duration of the mackerel fishery and the minimumtemperature observed at surface in the inshore sea-water during the south-westmonsoon period is discussed. Its usefulness in advance prediction of the durationof the fishery is indicated. The relation between the catch and the local rainfalland dissolved oxygen in the sea water is also dealt with.